Bandgap Restructuring of the Layered Semiconductor Gallium Telluride in Air. Issue 30 (12th May 2016) - Fonseca, Jose J.; Tongay, Sefaattin; Topsakal, Mehmet; Chew, Annabel R.; Lin, Alan J.; Ko, Changhyun; Luce, Alexander V.; Salleo, Alberto; Wu, Junqiao; Dubon, Oscar D.
Abstract : A giant bandgap reduction in layered GaTe is demonstrated . Chemisorption of oxygen to the Te‐terminated surfaces produces significant restructuring of the conduction band resulting in a bandgap below 0.8 eV, compared to 1.65 eV for pristine GaTe. Localized partial recovery of the pristine gap is achieved by thermal annealing, demonstrating that reversible band engineering in layered semiconductors is accessible through their surfaces.